Stone pine in Turkish forestry (Pinus pinea L.) (Theoretical and Applied Forestry, 2024)
This study was carried out on the Stone Pine (Pinus pinea L.) species, which is widely distributed in the world and in Turkey and has sociocultural, ecological, economic and aesthetic value in Turkish forestry. Stone pine wood, bark, resin and seeds called pine nuts are used. Pistachio pine is of great importance in the country's economy, both for its use in erosion control studies in sandy-arid areas and for production of pine nuts. Pine nuts are among the exported species classified as non-wood forest products. In 2023, $33,107,813 export revenue was obtained with 565 tons. As the versatile use of forests other than wood raw material increases day by day, and the Pistachio pine species subject to the study has such economic value and is naturally distributed in our country, the demand and applications for the species are also increasing.
Keywords: Pinus pinea; Pine nuts; Export; Silviculture